Q.[tex] \\ \\ [/tex]f(p) = p(p²) + p!! × 2pf(3) = …f(5) = …f(1) + f(2) = …[tex] \\ \\

by -13 views

f(p) = p(p²) + p!! × 2p

 \:

  • Kaki langit
    i
    l
    a
    i


    f
    (
    3
    )

f(3) = 3(3²) + 3!! × 2(3)

f(3) = 3(3 × 3) + (3 × 1) × (2 × 3)

f(3) = 3(9) + 3 × 6

f(3) = (3 × 9) + 3 × 6

f(3) = 27 + 3 × 6

f(3) = 27 + 18

f(3) =
4
5

  • N
    i
    l
    a
    i


    f
    (
    5
    )

f(5) = 5(5²) + 5!! × 2(5)

f(5) = 5(5 × 5) + (5 × 3 × 1) × (2 × 5)

f(5) = 5(25) + (15 × 1) × 10

f(5) = (5 × 25) + 15 × 10

f(5) = 125 + 15 × 10

f(5) = 125 + 150

f(5) =
2
7
5

  • N
    i
    l
    a
    i


    f
    (
    1
    )


    +


    f
    (
    2
    )

f(1) = 1(1²) + 1!! × 2(1)

f(1) = 1(1 × 1) + 1 × 2

f(1) = 1(1) + 1 × 2

f(1) = 1 + 1 × 2

f(1) = 1 + 2

f(1) = 3

f(2) = 2(2²) + 2!! × 2(2)

f(2) = 2(2 × 2) + 2 × (2 × 2)

f(2) = 2(4) + 2 × 4

f(2) = (2 × 4) + 2 × 4

f(2) = 8 + 2 × 4

f(2) = 8 + 8

f(2) = 16

f(1) + f(2)

= 3 + 16

=
1
9